Time series analysis of land use and land cover changes related to urban heat island intensity: Case of Bangkok Metropolitan area in Thailand - Dararat Khamchiangta; Shobhakar Dhakal (Journal of Urban Management, 2020)
This study focuses on time series analysis of land use and land cover (LULC) characteristics and its relationships with urban heat island (UHI) intensity in Bangkok Metropolitan area. The study is aimed at examining impact of LULC changes on the greenness and land surface temperature (LST) as well as the relationship of LST, LULC and Normalized difference vegetation index (NDVI). We consider the heat intensity, hot spot zones, and land use characteristics related hotspot areas. LULC classification based on satellite images taken by Landsat data in summer dates of 1991, 1997, 2005 and 2016, were classified into four LULC types: built up area; vegetation area; barren land; and surface water. UHI was studied by deriving LST based satellite images method using the thermal band of Landsat satellite in the same periods as of LULC classification. The results show that the built up area was approximately 30% in 1991, then, it was sharply increasing to approximately 55% of the total area in 2016. The changing trends of LST tend to be increasing while the value of NDVI with dense vegetation meaning tend to be declining over the study period. The significant negative correlation between LST and NDVI implied that the lower biomass can higher LST. UHI intensity was also continually rising from 11.91~êC in 1991 to 16.21~êC in 2016 leading to nearly 5~êC increase in Bangkok. High density of buildings, no vegetation areas and large area of concrete pavement are the most significant related to the hot spot areas.
Keywords: 710; Hot spot; Land surface temperature; Land use and land cover; Urban heat island; Städtische Flächennutzung; Umweltbelastung; Bangkok (Region); Thailand